Find Her: a Novel - Gardner, Lisa; Potter, Kirsten; Brilliance Audio (Firm) (Grand Haven, MI : Brilliance Audio, 2016)
When Boston detective D.D. Warren is called to the scene of a crime, a dead man and the bound, naked woman who killed him, she learns that Flora has tangled with three other suspects since her return to society. Is Flora a victim or a vigilante? And with her firsthand knowledge of criminal behavior, could she hold the key to rescuing a missing college student whose abduction has rocked Boston? When Flora herself disappears, D.D. realizes a far more sinister predator is out there. One who's determined that this time, Flora Dane will never escape. And now it is all up to D.D. Warren to find her.
Keywords: Warren, D. D. (Fictional character) -- Fiction; Police -- Fiction -- Massachusetts; Missing persons -- Fiction -- Investigation; Women college students -- Fiction; Vigilantes -- Fiction; Audiobooks; Boston (Mass.) -- Fiction; Detective and mystery fiction; Audiobooks